ANALISIS TINGKAT PAPARAN RADIASI DI AREA SETINGGI MATA DOKTER OPERATOR SELAMA PEMERIKSAAN DIAGNOSTIK CORONARY ANGIOGRAPHY DI RUANG CATHLAB - Devi Aprilia Primaningtyas; Soegardo Indra Praptono; Lailatul Muqmiroh (JRI (Jurnal Radiografer Indonesia), 2018)
Background : The radiation exposure of interventional cardiology can provide biological effects on patients and workers that is deterministic and stochastic effects. One organ that accepts the possibility of deterministic effects are the eyes. To find out the possibility of cataracts is measuring the level of radiation exposure in the area of radiation workers at eye level during the diagnostic coronary angiography procedures. Method: the measurement of the level of radiation exposure in the area of physician eye-level using a survey meter directly at the physician position. Measurements were made on the variation of the projection during diagnostic coronary angiography examination including PA-Cranial, LAO-Cranial, LAO-Caudal, RAO-Cranial, RAO-Caudal, RAO and LAO. Result: Measuring the level of radiation exposure in the area at physician eye-level during diagnostic coronary angiography obtained on sample A of 15.34 μSv for 69.17 seconds (1 minute 9.17 seconds and sample B of 25.11 μSv for 46 seconds. The total dose, DAP (dose Area Product) and fluoroscopy time of the operator A is higher than the operator B. Conclusion: The level of radiation exposure in the area of physician eye-level during diagnostic coronary angiography examination obtained does not exceed the dose limit value (NBD) is 75 μSv /h.